Mung Bean Supply Chain in Demak District, Central Java, Indonesia - Sri Suhartini; Iwan Aminudin; Zulmanery Manir (Syarif Hidayatullah State Islamic University Jakarta, 2022)
Mung bean production in Demak Regency is an export commodity to the Asian region which began to be developed more than 10 years ago, demand for exports is open as much as possible. Efforts to meet the demand required accuracy of quality and competitive production. For this reason, knowing the green bean supply chain is necessary. This research aims to analyze the product, money, and information flow of green beans in the Demak Regency. Using a descriptive research method using Purpose Sampling, research respondents in 3 districts had the most significant harvest area in the last 3 (three) years. The results showed that product flow consisted of 3 streams, namely 1) P – PP – PP/D – PB and K; 2) P - PP - PB - SE and 3) P - PP - SE, financial flows, namely consumers to production input shops and Exporter Suppliers to production input shops, while the flow of information runs from downstream to upstream and from upstream to downstream from farmers to exporters and vice versa as well as from farmers to consumers.